Histoenzymology and morphometry of the masticatory muscles of tufted capuchin monkey (Cebus apella Linnaeus, 1758) - Andreo, J. C.; Oliveira, J. A.; Navarro, J. A. C.; Roque, D. D.; Roque, J. S.; Buchain, R. L. (Department of Anatomy Keio University School of Medicine, 2002)
Samples of the anterior and posterior regions of the masseter and temporal muscles and of the anterior belly of the digastric muscle of 4 adult male tufted capuchin monkeys (Cebus apella) were removed and stained with HE and submitted to the m-ATPase reaction (with alkaline and acid preincubation) and to the NADH-TR and SDH reactions. The results of the histoenzymologic reactions were similar, except for acid reversal which did not occur in fibers of the fast glycolytic (FG) type in the mandibular locomotor muscles. FG fibers had a larger area and were more frequent in all regions studied. No significant differences in frequency or area of each fiber type were detected, considering the anterior and posterior regions of the masseter and temporal muscles. The frequency of fibers of the fast oxidative glycolytic (FOG) and slow oxidative (SO) types and of FOG area differed significantly between the anterior belly of the digastric muscle and the mandibular locomotor muscle. The predominance of fast twitch (FG and FOG) fibers and the multipenniform and bipenniform internal architecture of the masseter and temporal muscles, respectively, are characteristics that permit the powerful bite typical of tufted capuchin monkeys.
Keywords: Digastric muscle; Fiber types; Histoenzymology; Masseter; Masticatory muscles; Temporal muscle; Tufted capuchin monkey; adenosine triphosphatase; succinate dehydrogenase; tetrazolium reductase; animal; biopsy; Cebidae; cytology; enzymology; fast muscle fiber; histology; male; masticatory muscle; metabolism; physiology; slow muscle fiber; Adenosine Triphosphatases; Animals; Biopsy; Cebus; Male; Masticatory Muscles; Muscle Fibers, Fast-Twitch; Muscle Fibers, Slow-Twitch; NADH Tetrazolium Reductase; Succinate Dehydrogenase